Role of thromboelastography in predicting and defining pump thrombosis in left ventricular assist device patients. Issue 192 (August 2020) - Xia, Ranran; Varnado, Sara; Graviss, Edward A.; Nguyen, Duc T.; Cruz-Solbes, Ana; Guha, Ashrith; Krisl, Jill C.
Abstract: Introduction: Optimal anticoagulation for left ventricular assist device recipients aims to balance thrombosis and bleeding complications. Routine plasma-based coagulation tests may not accurately reflect overall hemostasis, and surrogate markers are used to help guide clinicians in the diagnosis of pump thrombosis. Thromboelastography derived coagulation index (CI) has been shown to be a parameter that can reflect "normocoagulability" in mechanical circulatory support device patients, but there is minimal data with regard to outcomes available. Our aim was to determine the role of CI in predicting and defining suspected pump thrombosis in HeartMate II™ recipients. Materials and methods: We performed a single center, retrospective longitudinal cohort study with a nested case-control analysis to compare serial CI values over time in adult HeartMate II™ recipients who had confirmed or suspected pump thrombosis to those who did not. Results and conclusions: A multivariate linear mixed model analysis of the suspected pump thrombosis versus no pump thrombosis groups found a significantly lower mean change in CI over time when recipients were followed for 24 months post-implant [0.71 (95% CI 0.1–1.32, p = .02)]; CI was first significant at six months. Within each arm, CI significantly decreased in the no pump thrombosis group, but did not significantly differ within the suspected pump thrombosis group. No significant differences were found between the two groups regarding the outcomes of death, transplant, or neurological events. Highlights: TEG derived coagulation index (CI) has been shown to represent "normocoagulability" in mechanical circulatory support patients We compared serial CIs over time in LVAD patients who had suspected pump thrombosis (PT) to those who did not Compared to non-PT group, suspected PT group had significantly higher mean changes in CI when followed to 24 months This suggests mean changes in CI may be useful in predicting suspected PT, and TEGs can be considered in routine follow-up